A Comprehensive Review of Tuberculosis in India: Incidence, Prevalence, Challenges, and Strategies for Elimination (International Journal of Pharmaceutical Sciences and Drug Research, 2025)
Especially in countries with lower and middle income levels like India, tuberculosis poses a serious worldwide health concern. Numerous individuals still get the disease every year despite advancements. The spread, causes, Global and national data and difficulties in diagnosing and treating tuberculosis in India are all examined in detail in this review. A major concern is latent tuberculosis infection, which can develop into active tuberculosis, particularly in people with weak immune systems, chronic illnesses like diabetes, or in high-risk environments such as prisons or healthcare settings. Drug-resistant in tuberculosis, including multidrug-resistant strains adds complexity to treatment efforts. Newer technologies, such as the Interferon-Gamma Release Assay (IGRA) and molecular diagnostics, hold promise despite the limitations of traditional diagnostic techniques like the Tuberculin Skin Test. Co-infections like HIV and social factors like poverty, nutrient deficiencies, and inadequate healthcare infrastructure are major contributors to the spread of tuberculosis.